Correlation between the Eosinophil Colonic Mucosa Density and Severity of Ulcerative Colitis - Aulia, Nisma; Mulya, Deshinta Putri; Bayupurnama, Putut; Ratnasari, Neneng (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: The inflammatory process of ulcerative colitis (UC) involves eosinophils. Eosinophils are not only related to the severity of UC but also to clinical improvement. The role of eosinophils in colonic mucosa has not been fully understood. This study aims to determine the correlation between the density of eosinophils in the colonic mucosa and the severity of ulcerative colitis.Method: This is a prospective cross-sectional study with consecutive sampling between August 2020 and July 2021. The subjects were UC inpatients/outpatients at Dr. Sardjito Hospital who met the inclusion and exclusion criteria. The number and location of the biopsies are determined based on a colonoscopy performed by a Gastroenterology-Hepatology Consultant. An Anatomic Pathology Specialist examined the eosinophil colonic tissue. The severity of UC was classified using the Truelove Witts score. Data analysis using a computer program with a p-value 0.05 was considered statistically significant.Results: There are 3 UC severity categories according to the Truelove Witts score: 22 mild (45.8%), 9 moderate (18.8%), and 17 severe (35.4%). Seven participants (14.6%) had eosinophilia, with a median eosinophilia score of 203.33 cells/microL (0–1470 cells/microL). Five participants (10.4%) with colonic mucosal eosinophilia, with a median value of 14.13 cells/HPF (0–172 cells/HPF). The density of colonic mucosal eosinophils and the severity of UC had a moderate connection (r = 0.396; p = 0.005).Conclusion: There is a significant correlation between the density of eosinophils in the colonic mucosa and the severity of UC.